Transcriptional Interactions of Single B-Subgenome Chromosome with C-Subgenome in B. oleracea-nigra Additional Lines - Pan Zeng; Xianhong Ge; Zaiyun Li (Plants, 2023)
Serial monosomic alien addition lines (MAALs) provide an ideal system to elucidate the transcriptomic interactions between the alien chromosomes and recipient genome under aneuploidy. Herein, five available Brassica oleracea-nigra MAALs (CCB1, CCB4, CCB5, CCB6, CCB8), their derived B. oleracea plants (non-MAALs), and two parents were analyzed for their gene expressions by using high-throughput technology. Compared to parental B. oleracea, all MAALs showed various numbers of DEGs, but CCB8 gave much higher DEGs; the number of downregulated DEGs was slightly higher than the number of upregulated ones, except for in relation to CCB8. All derived B. oleracea plants also gave certain numbers of DEGs, despite these being much lower than in the respective MAALs. Compared to B. nigra, in all five MAALs more DEGs were downregulated than upregulated. Trans-effects were likely more prevailing than cis-effects, and these DEGs were predominantly associated with material transport by dysregulating the cellular component. Meanwhile, the orthologous genes on alien chromosomes could only play a feeble compensatory role for those gene pairs in C-subgenome, and different levels of the expressed genes had a greater tendency towards downregulation. These results revealed transcriptional aneuploidy response patterns between two genomes and suggested that cis- and trans-mechanisms synergistically regulated alien gene transcriptions after distant hybridization.